Bioremediation: A sustainable approach for management of environmental contaminants - Singh P.; Singh V.K.; Singh R.; Borthakur A.; Madhav S.; Ahamad A.; Kumar A.; Pal D.B.; Tiwary D.; Mishra P.K. (My University, 2025)
The release of various inorganic and organic chemicals from various industries such as petrochemicals, textiles, pharmaceuticals, agro-based industries, and tanneries is highly toxic to the environment and human health. Several processes and technologies such as physical, chemical, and advanced oxidation processes are available for treatment of these pollutants. However, these processes and technologies have their own limitations and the end products are also of toxic nature. Therefore, there is a need for identifying and exploring sustainable and eco-friendly methods which require a lesser amount of chemicals, are economically feasible, and produce nontoxic end products. The bioremediation approaches to clean up environmental pollutants are considered as emerging and sustainable methods recently. Bioremediation process is based on an integrated approach employing microbial communities such as actinomycetes, bacteria, fungi, and earthworms. It is considered as a sustainable process for management of organic pollutants-rich solid wastes and wastewater. Many microorganisms metabolize toxic chemicals to produce CO2 or CH4, water, and biomass. These pollutants may be enzymatically altered to metabolites that are less noxious or innocuous. Moreover, the solid residue generated in this process has been found to have a potential influence on soil macro- and micronutrients, indicating its application as organic manure. However, bioremediation technique required more research for its establishment at a larger scale with an emphasis on the environmental consequences of the end products. In this chapter, we have performed a literature survey based on biological methods for the management of organic pollutants. Microbes responsible for degradation processes have also been presented in the later part of the chapter. In this chapter, a thorough understanding of the bioremediation processes and methods applied for abatement and remediation of organic pollutants has been described in detail. © 2020 Elsevier Inc. All rights reserved.